SILARIANG (KAWIN LARI) MENURUT PANDANGAN HUKUM ADAT DAN HUKUM ISLAM DAN DI KEC. PATTALLASSANG KAB. GOWA - laman, ilham (Jurnal Al-Qadau: Peradilan dan Hukum Keluarga Islam, 2022)
Fostering and building a household, has been regulated by law both Islamic law and with the law that exists in the community. The outbreak of the existing rules is not infrequently violated by two people who want to unite in domestic life, but sometimes get some obstacles. The purpose of holding research is to find out the problems of community related to marriage that does not go through the blessing of parents which results in the occupation of the mate (silaariang) in terms of the view of Islamic law and customary law in the Pattalassang District, Gowa Regency. This research uses the way of research, namely normative law through the framework of divinity or theological and sociological approaches. The results of the study provide information that the silariang in the Islamic legal view of the law is invalid, because the marriage that is carried out does not meet the legal elements, this also occurs without the existence of marriage guardians so that it cannot meet the legal requirements in a consent granted. Simply put it is concluded that elbows or with other names Silariang to the people of Gowa and around dikumi canceled. While Silariang in customary law in the Makassar Bugis community in Pattalassang District, Gowa Regency is seen as an act that brings siri (shame) if the act brings siri, the female family called Tumasiri has the right to take action against the Silariang perpetrators. For those who commit violations can be subject to sanctions, both in the form of minor sanctions such as exclusion and expulsion or severe sanctions, namely killed